HUBUNGAN BRAND IMAGE DENGAN LOYALITAS PASIEN DI INSTALASI RAWAT JALAN RSUP DR. TADJUDDIN CHALID - Noviani Munsir; Paramita Kurnia Wiguna; Andi Niartiningsih (MOTORIK Jurnal Ilmu Kesehatan, 2024)
Customer loyalty is very important in this era of intense competition. Customer loyalty is a customer's commitment to a brand, product or service based on a positive attitude that is reflected in consistent repeat purchases. The aim of the research is to determine the relationship between brand image and patient loyalty in the outpatient installation of Dr. Central General Hospital Tadjuddin Chalid. This type of research is quantitative using an analytical observational design with a cross sectional approach. The population in this study were all outpatient patients at RSUP Dr. Tadjuddin Chalid Makassar in 2022, namely 6278. Sampling was carried out using stratified random sampling with proportional random sampling of 170 respondents. The research results show that there is an influence of Brand Image on the loyalty of outpatients at RSUP Dr. Tadjuddin Chalid Makassar obtained a p value = 0.000 < 0.05. It is recommended for hospital management to improve its brand image by utilizing various electronic and social media to carry out promotions to further expand information about the big name of the hospital so that it is more widely known by the public, to expand parking lots and improve other hospital supporting facilities.